Drug Induced Rowell’s Syndrome: A Rare Presentation (Nepal Medical College Journal, 2024)
Rowell’s syndrome (RS) is a rare disorder characterized by Erythema multiforme (EM)-like lesions in a patient with lupus erythematosus, either systemic lupus erythematosus (SLE) or cutaneous lupus erythematosus (CLE). A 35 years old female presented in our dermatology outpatient department (OPD) with complaint of hemorrhagic crusting of lips and multiple discrete targetoid lesions over the chest, upper limb, and gluteal region. Investigations revealed a speckled pattern of antinuclear antibody (ANA), anti-Smith antibody, anti-ds DNA antibody, and strongly positive anti-Ro antibody. According to the clinical evaluation and investigations, the diagnosis of drug induced RS was made. The likely role of proton pump inhibitors, namely esomeprazole as a triggering factor is discussed. After stopping esomeprazole and starting medications with oral steroids and hydroxychloroquine, her good response to treatment was noted.